Gender dynamics in formal seed systems in Sub-Saharan Africa and worldwide lessons - Adams, Rahma (International Maize and Wheat Improvement Center, 2019)
Presented by Rahma Adams (International Maize and Wheat Improvement Center / CIMMYT) on 21 November 2019, as part of the webinar 'Gender dynamics in formal seed systems in Sub-Saharan Africa and worldwide lessons'. The webinar was co-organized by the CGIAR Collaborative Platform for Gender Research and CGIAR Research Program on Maize.